DOES GOD EXIST? THE LIMITED FREEDOM OF CHOICE ARGUMENT: A VOICE FROM AFRICA (AUN INTERNATIONAL CONFERENCE, 2025)
The talk about God is as old as man himself and the discourse is almost always centered on whether God exist or not. The contention has always been between theist – those who believe in the existence of God and atheist – who do not believe in the existence of God. The former comprises Judaism, Christianity, and Islam; they held the view that God exists. In Africa the question of the existence of God has never been in contention because Africans are deeply religious people. Although they hold various conceptions or ideas of God which vary from one ethnic group to another, all believe in the existence of a supreme being worthy of worship who controls the universe. It is an embarrassment for African people to publicly declare a disbelief in the existence of God. For Africans the belief in the existence of God is not debatable and so it does not need any rational justification or proof. They just accept by faith the traditional opinion that there is God; who is the creator of mankind and they are responsible to Him. This paper seeks to first examine the classical rational argument for God’s existence as postulated by western thinkers for the African community. The reason being that belief in God needs to be explicated and that demands rational process. Africans need rational justification for the belief in the existence of God. And the best place to start is to recast the classical traditional argument for the existence of God. Then the paper postulates a new version of argument for the existence of God based on CHOICE. This voice from African thinker makes a novel contribution to the global discussion on the question Does God Exist?  The paper analytically describes the major arguments of God’s existence, and analyses critically and logically the premises of their truth claims.